Magmatic processes recorded in plagioclase and the geodynamic implications in the giant Shimensi W–Cu–Mo deposit, Dahutang ore field, South China. (1st June 2021) - Fan, Xianke; Zhang, Zhiyu; Hou, Zengqian; Mavrogenes, John; Pan, Xiaofei; Zhang, Xiang; Dai, Jialiang; Wu, Xianyuan
Highlights: The two magma chambers experienced chemically closed magmatic evolution. The calcium needed for the scheelite mineralization may have been provided by the BG. The highly evolved felsic magma chamber is critical to the formation of the giant Shimensi deposit. Abstract: The Shimensi W–Cu–Mo deposit is one of the largest tungsten deposits in the world. Despite numerous geochemical studies conducted on ore-related granites in the district, few studies have concerned magma chambers processes. In this study, systematic in-situ major- and trace-element studies across plagioclase crystals from the ore-related Mesozoic granites as well as whole-rock Sr–Nd isotopic compositions of such granites in the Shimensi deposit were used to constrain the sources of calcium, the dynamics of the magmatic system and the metallogenic geodynamic setting. In-situ analyses of plagioclase showed no obvious positive correlations between An and FeO, while Sr was positively correlated with Ba, indicating that the magma chambers in the Shimensi deposit may have experienced chemically-closed evolution affected only by thermal mixing and/or decompression, without chemical mixing with mafic magma from the mantle. This conclusion was also supported by whole-rock Sr–Nd isotopic characteristics of high ( 87 Sr/ 86 Sr)i (0.71664–0.73689) and negative εNd (t) values (−9.81 to −5.07). It was found that the calcium needed for scheelite mineralization may have been predominantly provided by biotite granodiorite (BG) because of its high calcium content and large size, while ore-forming metals should mainly have been derived from the magma sources of pelites and basic volcanic rocks in the Shuangqiaoshan Group instead of the recharging of mafic magma. Moreover, change of the stress environment likely facilitated the formation of long-term stable, large-volume, highly evolved felsic magma chambers in the shallow crust, which would have been critical to the formation of the giant Shimensi W–Cu–Mo deposit.